Extraction of secondary metabolites, phytochemical screening and the analysis of antibacterial activity in stevia rebaudiana - Zohra, Fatima Tuz (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Bachelor of Science in Biotechnology, 2015.